2019
DOI: 10.1002/jctb.6090
|View full text |Cite
|
Sign up to set email alerts
|

Selective conversion of furans to p‐xylene with surface‐modified zeolites

Abstract: BACKGROUND Owing to the growing consumption of oil and the negative environmental impacts, the production of p‐xylene (PX) from renewable biomass has gained significant attention recently. However, the major challenge for the production of PX from biomass or furans is how to improve the yield and selectivity of PX, along with reducing coke. RESULTS The para selectivity in the catalytic conversion of furans was greatly enhanced owing to the deactivation of external surface and the adjustment of pore entrance. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…Methanol itself can also form aromatics through the aromatization reactions (Fig. 3), which is consistent with previous work (Zhu et al 2019). Previous studies showed the overall yield of aromatics increased for the co-catalytic conversion of furan/methanol (Zhu et al 2019;Zheng et al 2014) or biomass/methanol over HZSM-5 (Zhang et al 2012).…”
Section: Effects Of Reaction Parameters On Production Of Toluene Intermediatesupporting
confidence: 91%
See 2 more Smart Citations
“…Methanol itself can also form aromatics through the aromatization reactions (Fig. 3), which is consistent with previous work (Zhu et al 2019). Previous studies showed the overall yield of aromatics increased for the co-catalytic conversion of furan/methanol (Zhu et al 2019;Zheng et al 2014) or biomass/methanol over HZSM-5 (Zhang et al 2012).…”
Section: Effects Of Reaction Parameters On Production Of Toluene Intermediatesupporting
confidence: 91%
“…In order to analyze the catalyst's crystal phase, X-ray diffraction (XRD) spectra were gained by using an X'pert Pro-Philips diffractometer (Philips in Netherlands) (Zhu et al 2019). XRD patterns were obtained using the Cu K radiation (0.15406 nm) at 45 kV and 40 mA, which were scanned in the range of 5°\ 2h \ 80°.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, not all furanics were equally converted. A comparison of 2,5-dimethylfuran (DMF), furan, and furfural revealed that electron-rich DMF quickly reacted while the electron-deficient furfural lagged behind: DMF > furan > furfural [94]. In addition to aromatics, CO 2 , CO, and other olefins were also made at 400-600 °C [38].…”
Section: Catalytic Co-pyrolysis (Ccp)mentioning
confidence: 99%
“…Some studies have indicated that a simultaneous saccharification and fermentation process is more advantageous in contrast to carrying out these steps separately, because the yields obtained are higher, only one tank is required, and the operation time is shorter. [ 88,261 ] The increase in yield is mainly due to the fact that glucose is rapidly transformed into bioethanol, avoiding its inhibitory effect on hydrolytic enzymes, which increases glucose yield and increases the availability of substrate for alcoholic fermentation. However, simultaneous saccharification and fermentation requires the optimization of parameters such as temperature, pH, and enzymatic concentrations, since the optimal temperature and pH, as well as the fermentation strains are different in the two processes.…”
Section: Processing Of Fvwmentioning
confidence: 99%